The clinical spectrum of idiopathic hyperuricosuria in children: Isolated and associated with hypercalciuria/hyperoxaluria - Kamal Akl; Redab Ghawanmeh (Saudi Journal of Kidney Diseases and Transplantation, 2012)
The clinical manifestations of hyperuricosuria (HU) are usually underestimated by the clinician. The aim of this study was to review the clinical spectrum of symptomatology of HU and to evaluate the presence of associated hypercalciuria (HC) and hyperoxaluria (HX). A retrospective review was done on 64 children with HU seen between January 2004 and December 2008. The patients were divided into HU 19, HU + HC 4, HU + HX 21 and HU + HC + HX 20. The mean age at diagnosis was 80 months (range six to 156 months). Duration of follow-up ranged was from six to 66 months. There were 228 symptomatic episodes for 64 patients (males 31, females 33). The relationship of symptomatology to age and gender were not significant. The most common symptoms were abdominal pain 67.2% (in 7/44 it was localized to the right lower quadrant, mimicking appendicitis), flank pain 59.4%, increased urinary frequency 43.4%, urgency 39%, enuresis 31.25%, oliguria 29.7%, dysuria 25%, red urine 20.35%, vaginal itching 15.21%, dribbling 14.06%, orange urine 12.5%, hesitancy 12.5% and penile pain 7.81%. To our knowledge, the vaginal itching and penile pain were not previously described. Family history was positive for stones and/or gout in 62.5%. The presence of a positive family history and red urine were significant (P-value <0.05) for the presence of an underlying HU. In the presence of recurrent abdominal/flank pain, hematuria without proteinuria or edema and urological symptomatology, especially in the presence of red urine, and a positive family history of gout or stones, a search for HU is in order. This will avoid unnecessary and invasive investigations.